2018
DOI: 10.5414/cn109471
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a remote monitoring system of healthcare resource consumption in patients on automated peritoneal dialysis (APD): A simulation study

Abstract: Aims: Remote monitoring (RM) can improve management of chronic diseases. We evaluated the impact of RM in automated peritoneal dialysis (APD) in a simulation study. Materials and methods: We simulated 12 patient scenarios with common clinical problems and estimated the likely healthcare resource consumption with and without the availability of RM (RM+ and RM– groups, respectively). Scenarios were evaluated 4 times by randomly allocated nephrologist-nurse teams or nephrologist-alone assessors. Results: The RM+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…Based on our synthesis, it can be argued that telehealth interventions, and RPM in particular, could potentially reduce hospitalization rates, as well as healthcare resource consumption in terms of hospitalization length and the number of in-person visits. This is consistent with several other reports in which RM-APD was evaluated [ 40 42 ]. These reports were excluded from this review, because these concerned simulation studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on our synthesis, it can be argued that telehealth interventions, and RPM in particular, could potentially reduce hospitalization rates, as well as healthcare resource consumption in terms of hospitalization length and the number of in-person visits. This is consistent with several other reports in which RM-APD was evaluated [ 40 42 ]. These reports were excluded from this review, because these concerned simulation studies.…”
Section: Discussionsupporting
confidence: 93%
“…Six studies evaluated associations between telehealth interventions and transfer to hemodialysis [ 16 , 21 , 28 , 31 , 34 , 40 ]. These studies comprise a total of 8054 participants, with an average age of 58.6 ± 7.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…This method of monitoring also makes it possible to record any interruptions in treatment by the patient or any time the prescribed treatment is not completed as an indication of unsatisfactory compliance [2]. These advantages can be demonstrated not only in the clinical area in terms of better dialysis compliance, metabolic stability, reduction of complications but are also potential advantages in the management area with reduction of unplanned activities and hospitalizations with economic advantages as studied in an ongoing trial and simulation studies [12][13][14]. Indeed, the use of remote monitoring in different types of chronic home-care patients has demonstrated, in published studies, significant clinical, economic, and social benefits including a reduction in emergency room admissions, hospitalizations associated with treatment, and transfers from home to the hospital with an improvement in the quality of care and the satisfaction of the patient and his/ her care-helper or caregiver [3,4,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…While the advantages seem obvious, studies with objective outcomes are few and often hampered by small sample size, heterogeneous populations or other study limitations. Some authors reported reduced unplanned hospital and emergency room visits with an associated reduction in utilization and cost of health resources, but no change in overall hospitalization rates [ 23 , 24 ]. Wallace et al .…”
Section: Dialysismentioning
confidence: 99%